Adenylyl Cyclase 6 Mediates Inhibition of TNF in the Inflammatory Reflex - Tarnawski, Laura; Reardon, Colin; Caravaca, April S.; Rosas-Ballina, Mauricio; Tusche, Michael W.; Drake, Anna R.; Hudson, LaQueta K.; Hanes, William M.; Li, Jian Hua; Parrish, William R.; Ojamaa, Kaie; Al-Abed, Yousef; et al. (Frontiers in Immunology, 2018)
Macrophage cytokine production is reflexively mediated by neural circuits. One example is the inflammatory reflex, defined by electrical signals traveling in the vagus nerve and signaling through splenic choline acetyltransferase+ T cells. Lymphocyte acetylcholine is the ligand for alpha7 nicotinic acetylcholine receptors (α7nAChR) on macrophages that suppress TNF release. Here, we observed that electrical vagus nerve stimulation of the inflammatory reflex with a duration of 0.1s - 60s significantly reduced systemic TNF release in endotoxemia. This suppression of TNF was sustained for more than 24 hours, but abolished in mice deficient in the α7nAChR subunit. Exposure of primary human macrophages and murine RAW 264.7 macrophage-like cells to selective ligands for α7nAChR for one hour in vitro attenuated TNF production for up to 24 hours in response to endotoxin. Pharmacological inhibition of adenylyl cyclase (AC) and knockdown of adenylyl cyclase 6 (AC6) or c-FOS abolished cholinergic mediated suppression of endotoxin-induced TNF release. These findings indicate that action potentials in the inflammatory reflex trigger an extended change in macrophage activation behavior that requires AC and phosphorylation of cAMP response element binding protein (CREB). This has significant implications for mechanisms of bioelectronic therapies to treat inflammatory diseases.